Attitudes and knowledge about naloxone and overdose prevention among detained drug users in Ningbo, China - Liu Yu; Bartlett Nicholas; Li Longhui; Lv Xiuyi; Zhang Yahai; Zhou Wenhua (BMC, 2012)
Abstract Background To date there has been limited research on both the prevalence of overdose and drug user knowledge about overdose prevention and response methods in China. In addition, there has been no effort to integrate naloxone information and distribution into pre-release services for drug users detained in isolated compulsory detoxification facilities in China. Methods The authors conducted a survey of 279 heroin users in isolated compulsory detoxification centers in Ningbo, China in an attempt to evaluate the possibility of conducting prelease peer naloxone programs in Ningbo isolated compulsory detoxification centers. Respondents' demographic background, history of heroin overdoses, and attitudes/knowledge about overdose prevention and response were collected. Results While drug users in Ningbo's compulsory detoxification centers have limited understandings of how to effectively respond to overdoses, they expressed concern about the possibility of overdose, interest in participating in overdose prevention and response programs, and a willingness to help their peers. In general, there was no significant difference in history and attitudes/knowledge of overdose between male and female participants. Conclusion Based on the findings of this research, our survey provides preliminary evidence that detained drug users have considerable interest in overdose prevention and response information and willingness to help peers. However, drug users in Ningbo isolated compulsory detoxification centers currently have limited understandings of effective ways of helping to prevent overdose deaths.